2021
DOI: 10.3390/insects12080681
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Effects of a Neonicotinoid and a Novel Sulfoximine Insecticide on the Harlequin Ladybird

Abstract: The harlequin ladybird, Harmonia axyridis Pallas (Coleoptera: Coccinellidae), is a generalist predator and an effective biocontrol agent of various insect pests that has been exploited for the control of aphid pests in the greenhouse and field. However, insecticides are widely used to control aphid pests worldwide and the potential non-target effects of sulfoxaflor and imidacloprid for controlling aphid pests towards this biocontrol agent are little known. Although both sulfoxaflor and imidacloprid act on nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
1
13
0
1
Order By: Relevance
“…Additionally, we exposed aphids to fungicides at a single time point to ensure all aphids were at the same development stage but exposing aphids at multiple time points or at different life stages may have resulted in different findings. Past studies have demonstrated the impact of pesticides, and other stressors, can depend on the life stage exposure occurs 87,97,98 . Future work testing if endosymbionts are more vulnerable to fungicides (or other treatments) at a particular aphid life stage would be informative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we exposed aphids to fungicides at a single time point to ensure all aphids were at the same development stage but exposing aphids at multiple time points or at different life stages may have resulted in different findings. Past studies have demonstrated the impact of pesticides, and other stressors, can depend on the life stage exposure occurs 87,97,98 . Future work testing if endosymbionts are more vulnerable to fungicides (or other treatments) at a particular aphid life stage would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…While our study is the first, to our knowledge, to show that fungicides have transgenerational effects on aphids, we can compare our findings to other studies that have shown multiple pesticides (including insecticides and herbicides) may have non-target effects on insects that manifest over multiple generations. [84][85][86] Transgenerational effects are rarely considered by farmers when they use fungicides or other pesticides, 87 but may provide greater pest management options. 81 For instance, if a single fungicide spray has deleterious impacts on a pest population that persists over generations, fewer applications of pesticides may be required to keep pest densities below economic threshold levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers, however, often lack IPM expertise, and because of the advantages of simpleness and convenience, farmers tend to apply insecticides at higher than recommended concentrations and do so periodically rather than being based on pest density as revealed by scouting (Zhou et al 2014). Such pest control practices have increased the level of insecticide resistance of key pests and harmed natural enemy levels, which ultimately compromises pest management efficacy and agricultural resilience (Liu et al 2019, Yang et al 2019, Dai et al 2020, 2021). For example, Janssen and van Rijn (2021) showed that increasing insecticide use levels did not necessarily lower pest populations any further in the presence of effective natural enemies.…”
Section: Introductionmentioning
confidence: 99%
“…Sublethal effects of imidacloprid have been reported in many insects, e.g., affecting biological performances, changing enzyme activities or influencing gene expression [19][20][21]. Several studies suggested that the sublethal concentrations of imidacloprid negatively affected fecundity in exposed insects, such as Bemisia tabaci [22], Sogatella furcifera [23], Rhopalosiphum padi [20], Harmonia axyridis [24], and Ceratomegilla undecimnotata [25]. However, exposure to low concentrations of imidacloprid could benefit several insects, including Aphis glycines [26] and Myzus persicae [27].…”
Section: Introductionmentioning
confidence: 99%